THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN ELECTION SUPERVISION: BETWEEN DIGITAL EFFECTIVENESS AND THE PROTECTION OF CITIZENS’ POLITICAL RIGHTS - Erfan Wahyudi; Wiredarme (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2024)
This study examines the application of artificial intelligence in Indonesian election supervision, focusing on the balance between digital effectiveness and the protection of citizens’ political rights. The objective is to analyze how AI can support the monitoring of electoral violations, hoaxes, deepfakes, digital campaigns, and voter-data risks without weakening democratic principles. This research applies a qualitative legal method with normative-juridical, conceptual, and socio-legal approaches. The analysis is based on constitutional principles, election law, campaign regulations, personal data protection law, election supervisory regulations, and recent scholarly debates on AI, disinformation, deepfakes, and electoral integrity. The findings show that AI may strengthen election supervision by improving the speed, scale, and accuracy of digital monitoring. Yet AI may also create constitutional risks, including wrongful content classification, suppression of legitimate political expression, unequal enforcement, excessive surveillance, privacy violations, and wrongful voter-data profiling. This study argues that AI-based election supervision is constitutionally legitimate only when it is governed by legality, proportionality, transparency, accountability, and meaningful human oversight. The contribution of this study lies in framing AI in election supervision as a constitutional issue concerning political rights, democratic accountability, and electoral integrity, rather than merely as a technological tool for detecting violations.